Aksyaa – Aplikasi Sistem Informasi Akuntansi berbasis Android - Bayu Hermawan; Giri Wahyu Wiriasto; Lalu A. Syamsul Irfan Akbar (Journal of Computer Science and Informatics Engineering (J-Cosine), 2023)
Today the development of software technology in the field of accounting is increase rapidly following the trend of using mobile devices and the increasing number of new business actors. Prior to this research, we proposed an Accounting Information System (AIS) that runs on a web platform as the main server. The development of this mobile application also uses the same database as the web version running on a dual-platform, web server and mobile based. The Application Programming Interface (API) was developed on the AIS system with the RESTFul method as an integration medium using the HTTP Hyper-Text Transfer Protocol protocol between web and mobile bases in a case study of a company's transaction data. Furthermore, techniques for using the API have described on the development side of the mobile interface. Communication in HTTP is centered on the request response cycle, where the request is the process of requesting data from the server and the response is the data sent by the server according to the client's request. Based on testing the integration process, the information displayed on the mobile version of the application can work properly. Likewise, testing was carried out by entering transaction data into the system as many as 798 records with 141 account lists provided. As a result, the display of the mobile page shows that all features are able to work and display the same output data as AIS on the web version, including features for reports on purchases and sales of goods, cash flow, general ledger, trial balance, and income statement.